MUSCLE-SPARING VERSUS STANDARD POSTEROLATERAL THORACOTOMY IN NEONATES WITH ESOPHAGEAL ATRESIA - ASKARPOUR,Shahnam (2018)
ABSTRACT Background : The muscle-sparing thoracotomy (MST) has not yet been thoroughly studied and assessed in comparison to the traditional thoracotomy method in newborns. Aim : To compare the outcomes of MST and standard posterolateral thoracotomy (PLT) in newborns. Methods : Randomized, controlled, double-blind trial on 40 neonates with esophageal atresia, comparing the time of beginning a surgery until seeing the pleura, the duration of hospitalization in the neonatal intensive care unit, the time in ventilator, the time of returning the shoulder function, the time of returning the Moro reflex, and the mortality between the two techniques. Results : The data showed no differences between the two groups in basic information (weight, height, gender, numbers of prematurity neonates and caesarean). The results on the size of the scar in the MST group was significantly lower than in the PLT group. Also, the time of returning the shoulder function in MST group was earlier than in PLT group. There were no significant differences in the duration since the beginning the surgery to see the pleura, the time of being hospitalized in intensive unit, the time that the infant required ventilator, returning time of the Moro reflex in 1st and 3rd months after the operation, and the mortality rates between MST and PLT groups. Conclusion : It seems that the advantages of using MST over PLT procedure in neonates include the earlier shoulder function recovery and also superior cosmetic results.